Fibromyalgia Syndrome in Patients with Chronic Low Back Pain - İlker Yağcı and Eylem Akcan and Pelin Yıldırım and Mehmet Ağırman and Zeynep Güven (Archives of Rheumatology, 2010)
Objective: To determine the incidence of fibromyalgia syndrome (FMS) in patients with chronic low back pain (CLBP) and to compare the characteristics of patients with only CLBP and patients with CLBP and FMS. Materials and Methods: Fifty five patients with CLBP were enrolled to the study. The low back pain was assessed with Visual Analog Scale (VAS), emotional, social and physical health conditions were assessed with Nottingham Health Profile (NHP), general health condition was assessed with Health Assessment Questionnare (HAQ) and severity of depression was assessed with Beck Depression Inventory (BDI). Results: The diagnosis of FMS was estabilished in 15 of 55 (27.3%) patients with CLBP according to American College of Rheumatology criteria. VAS and HAQ scores were higher (p=0.014 and p=0.017 respectively), energy level of NHP was lower (p=0.009) in patients with FMS when they were compared to patients with only CLBP. There were not any significant differences in BDI between groups. Conclusion: The VAS scores of patients with CLBP and FMS were higher and energy levels of this group were lower. These results should be considered while making treatment programs. (Turk J Rheumatol 2010; 25: 37-40)